Saúde mental de servidores públicos : avaliando um programa de intervenção para dor - Monteiro, Bárbara Kolstok (Universidade Federal de São Carlos, 2015)
Pain disorders are usually related to lower level of general health, quality of life and poores work performance. Brazilian studies show that pain disorders have been described as the second or third leading cause of absence from work. Therefore this replication study was conducted to evaluate a brief intervention program developed by Nash et al (2004) that could be implemented in companies or organizations, which would represent an important advance in dealing with this problem. This study aimed to evaluate the effects of a brief intervention protocol, using behavioral and cognitive-behavioral techniques for administrative employees with chronic pain diagnoses. The impacts were evaluated along three dimensions: 1) self-perception of both pain and work impacts; 2) mental health indicators, including measures of depression, anxiety and stress; and 3) measures of functionality and quality of life. The study included five public service workers, between 36 and 61 years of age. Three women had been diagnosed with Fibromyalgia, one with Migraines and the other with neuritis. Time since diagnosis ranged from 2 to 7 years. The intervention was programmed using a multiple baseline procedure in four phases: 1) Baseline; 2) Module 1 (Psychoeducation about pain processes); 3) Module 2 (Relaxation Techniques); and 3) Module 3 (Stress and coping strategies). During the Initial Evaluations and over the course of the intervention, the following instrumentes were used: General Interview, Inventory of Stress Symptoms for Adults - Lipp (ISSL), Beck Depression and Anxietyies Inventory, FAST and the WHOQOL-BREF Scale. The Individual records showed a correlation between the intensity of pain and effectiveness in working conditions in general (r = 0.86, p <0.001) and for each of the participants. It was possible to observe the effect of the intervention at different times, for all participants. Initially, all participants had health care needs related to stress (four presented scores of resistance and one of almost exhaustion). Two had health care needs related to depression (P4 and P6) and two had process related to anxiety (P2 and P4). One participant (P4) had health care needs on all three measures. With regards to functionality, three respondents reported having difficulty in performing cognitive activities and one of the participants reported having difficulties in both controlling money and managing daily financial routines. The participants had average scores close to 50 points in the four areas assessed by the WHOQOL-BREF. Following the intervention, three of the five subjects had an increase in their total score for quality of life. Four participants also reported less difficulty with functionality, considering all the domains evaluated, with better performance observed in the autonomy domain. The strong points of the protocol were discussed along with challenges in its execution. Further research are needed to.
Public worker’s mental health and quality of life : evaluating a chronic pain intervention protocol
Keywords: Dor crônica; Qualidade de vida; Indicadores de saúde mental; Chronic pain; Behavioral intervention protocol; Workers health; Quality of life; Indicators of mental health; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL